HUBUNGAN ADIPONEKTIN DENGAN GAGAL JANTUNG KONGESTIF - Agung Budiyasa, Dewa Gde; Santoso, Anwar (journal of internal medicine; Vol. 9, No. 3 September 2008)
Adipose tissue synthesis several protein involved in the regulation of insulin action and lipid metabolism. Among the protein adipocytokines, adiponectin is the most abundant and exerts profound anti-diabetic, anti-atherogenic, and anti-inflammatory roles. Adiponectin may contribute to the regulation of vascular hemostasis by its ability to affect several signaling pathways in the vessel wall and modulate excess inflammatory responses. In the heart, adiponectin serve as a regulator of cardiac injury through modulation of pro-survival reaction, cardiac energy metabolism, and inhibition of hypertropic remodelling. Many effect of adiponectin in the cardiovascular system correlate with the activation of both AMPK and Cox-2. Adiponectin levels may influence the development of CHF, but the epidemiological data are somewhat complex. This is due in part to the fact that while higher body mass indices are a risk factor for heart failure, obesity is a predictor of improve prognosis in patients with establish CHF because wasting is strongly associated with the increased risk of death in the final stage of this disease. In this regard, high adiponectin levels are a predictor of mortality in patients with heart failure. Presumably, this paradoxical relationship exist because high body mass, hence low protein, favors survival in endstage heart failure. Therefore, further studies should examine adiponectin levels in patients with stable heart failure
Keywords: adiponectin, heart failure